1993
DOI: 10.1123/jab.9.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Landing Strategy Adjustments Made by Female Gymnasts in Response to Drop Height and Mat Composition

Abstract: In this study, drop height and landing mat composition were hypothesized to influence the landing strategies preferred by female gymnasts. Adjustments in strategy in response to changes in drop height and mat composition were identified by comparison of mechanical variables characterizing two-foot competition-style drop landings from three heights onto two different mats varying in composition (i.e., soft vs. stiff). Force-time characteristics of the landings were quantified (1000 Hz) by a force plate fully su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 14 publications
3
43
0
3
Order By: Relevance
“…Ground impact forces generally increase with greater drop height (Dufek and Bates, 1990;McNitt-Gray et al, 1993) and greater impact forces suggest a greater injury risk to the lower extremity. The landing strategies of the gymnast and the landing mat characteristics have been identified as key factors in the dissipation of forces during landing (Dufek and Bates, 1990;McNitt-Gray et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground impact forces generally increase with greater drop height (Dufek and Bates, 1990;McNitt-Gray et al, 1993) and greater impact forces suggest a greater injury risk to the lower extremity. The landing strategies of the gymnast and the landing mat characteristics have been identified as key factors in the dissipation of forces during landing (Dufek and Bates, 1990;McNitt-Gray et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ground impact forces generally increase with greater drop height (Dufek and Bates, 1990;McNitt-Gray et al, 1993) and greater impact forces suggest a greater injury risk to the lower extremity. The landing strategies of the gymnast and the landing mat characteristics have been identified as key factors in the dissipation of forces during landing (Dufek and Bates, 1990;McNitt-Gray et al, 1993). A gymnast can voluntarily modulate the external loading experienced during impact, therefore it may be possible for the gymnast to minimise the internal forces by altering the muscle recruitment/activation patterns (McNitt-Gray et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Ground reaction forces of up to 12 times body weight have been reported during participation in gymnastics. (10) One limitation of cross-sectional studies is that solid conclusions cannot be drawn about how group differences emerged. Childhood and adolescence are key stages for BMD development since nearly all of adult bone mass is achieved by the end of adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Impact forces acting on the human body during landing must be dissipated primarily by the musculoskeletal system and excessive loading may result in injury (McNitt-Gray et al, 2000). Previous experimental research has focused on landing from various drop heights (DeVita and Skelly, 1992;Dufek and Bates, 1990;McNitt-Gray et al, 1993 and1994;Ozguven and Berme, 1988). The results have shown that the amount of joint flexion, rate of joint flexion, landing phase duration, and ground impact forces generally increased with greater drop height.…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that the amount of joint flexion, rate of joint flexion, landing phase duration, and ground impact forces generally increased with greater drop height. Factors affecting the dissipation of forces during landing have been identified as the landing strategy (Dufek and Bates, 1990;McNitt-Gray et al, 1993) and the landing mat (McNitt-Gray et al, 1994). Landing mats undergo large amounts of area deformation and are now essential for landings from gymnastics apparatus dismounts and vaults.…”
Section: Introductionmentioning
confidence: 99%